2018
DOI: 10.1128/jcm.01822-17
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence Analysis of Streptococcus pneumoniae Strains That Cause Hospital-Acquired Pneumonia Infections

Abstract: colonizes the nasopharyngeal mucus in healthy individuals and can cause otitis media, pneumonia, and invasive pneumococcal diseases. In this study, we analyzed strains that caused 19 pneumonia episodes in long-term inpatients with severe underlying disease in a hospital during a period of 14 months (from January 2014 to February 2015). Serotyping and whole-genome sequencing analyses revealed that 18 of the 19 pneumonia cases were caused by strains belonging to 3 genetically distinct groups: clonal complex 9999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…In Taiwan, while ST338 and ST166 accounted for the majority (74.5%, 35/47) and minority (6.4%, 3/47) of serotype 23A isolates, respectively, during 2012-2014 in one hospital (Su et al, 2015), we observed an increase of a serotype 23A-ST166 MDR meropenem-resistant clone in patients from different hospitals during 2016-2018. ST166 has been associated with serotype 9V isolates in Taiwan, Japan, and Korea before 2014 (Hsieh et al, 2009;Su et al, 2015;Chang et al, 2018;Yun et al, 2018), and in serotype 11A isolates from Korea and Japan more recently (Chang et al, 2018;Kim et al, 2019). However, only one isolate from Japan and two ceftriaxone-nonsusceptible isolates from Korea with the serotype 23A-ST166 combination have been described so far but their meropenem susceptibility is unknown (Chang et al, 2018;Choi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Taiwan, while ST338 and ST166 accounted for the majority (74.5%, 35/47) and minority (6.4%, 3/47) of serotype 23A isolates, respectively, during 2012-2014 in one hospital (Su et al, 2015), we observed an increase of a serotype 23A-ST166 MDR meropenem-resistant clone in patients from different hospitals during 2016-2018. ST166 has been associated with serotype 9V isolates in Taiwan, Japan, and Korea before 2014 (Hsieh et al, 2009;Su et al, 2015;Chang et al, 2018;Yun et al, 2018), and in serotype 11A isolates from Korea and Japan more recently (Chang et al, 2018;Kim et al, 2019). However, only one isolate from Japan and two ceftriaxone-nonsusceptible isolates from Korea with the serotype 23A-ST166 combination have been described so far but their meropenem susceptibility is unknown (Chang et al, 2018;Choi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ST166 has been associated with serotype 9V isolates in Taiwan, Japan, and Korea before 2014 (Hsieh et al, 2009;Su et al, 2015;Chang et al, 2018;Yun et al, 2018), and in serotype 11A isolates from Korea and Japan more recently (Chang et al, 2018;Kim et al, 2019). However, only one isolate from Japan and two ceftriaxone-nonsusceptible isolates from Korea with the serotype 23A-ST166 combination have been described so far but their meropenem susceptibility is unknown (Chang et al, 2018;Choi et al, 2019). Together, these observations suggested emergence of MDR meropenem-non-susceptible serotype 15A-ST63 isolates in different countries, and possible capsular switching of ST166 to serotype 23A isolates followed by local spread of MDR meropenem-resistant serotype 23A-ST166 clone in Taiwan, both of which raise concern since neither serotype is included in the current PCV13.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, WGS has increased power to establish the evolutionary relationships between close strains across the species [9]. Multiple studies have used the high-throughput WGS to investigate PCV impact and clustering pneumococcal populations into groups using genomic variation that reflect a recent evolutionary history [10][11][12][13]. The objectives of this study, as part of the Pneumococcal African Genome project (PAGe), were to determine the phylogenetic relationships of serotype 1 isolates recovered from children patients in Casablanca, compared to isolates from other African countries (Egypt, Ethiopia, Ghana, Malawi, Mozambique, Niger, Nigeria, South Africa and The Gambia), and to investigate the contribution of accessory genes and recombination events to the genetic diversity of this serotype.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the WGS has increased power to establish the evolutionary relationships between close strains across the species [9]. Multiple studies have used the high-throughput WGS to investigate PCV impact and clustering pneumococcal populations into groups using genomic variation that re ect a recent evolutionary history [10][11][12][13]. The objectives of this study, as part of the Pneumococcal African Genome project (PAGe), were to determine the phylogenetic relationships of serotype 1 isolates recovered from children patients in Casablanca, compared to isolates from other African countries (Egypt, Ethiopia, Ghana, Malawi, Mozambique, Niger, Nigeria, South Africa and The Gambia), and to investigate the contribution of accessory genes and recombination events to the genetic diversity of this serotype.…”
Section: Introductionmentioning
confidence: 99%